Appropriateness of surgical antibiotic prophylaxis for breast surgery procedures - Jaber, S.; Rogers, C.; Sunderland, B.; Parsons, R.; MacKenzie, S.; Seet, J.; Czarniak, Petra (Springer Netherlands, 2017)
© 2017, Springer International Publishing.Background Guidelines for the appropriate use of antibiotic prophylaxis are provided in the Therapeutic Guidelines: Antibiotics (eTG) in Australia. Inappropriate use of antibiotics is problematic. Objective To examine adherence with therapeutic guidelines (eTG) in breast surgery and trends in non-adherence dependent on the type of breast surgery performed. Setting Major Western Australian teaching hospital. Method A retrospective cross-sectional study reviewed a random sample of 150 from 1049 eligible medical records of patients who underwent a breast surgical procedure in 2013 or 2014. Main outcome measure Adherence to the eTG. Results Antibiotic prophylaxis was prescribed for 139 (92.7%) operations. Adherence to the eTG occurred in 20 (13.3%) operations, whilst 11 (7.3%) did not adhere to any element of the eTG. Appropriate timing was the main factor not adhered to. Postoperative antibiotics were prescribed following 35 (23.3%) operations, with 32 (91.4%) administered beyond 24 h. Length of stay was significantly different (p = 0.0036) between surgical groups. There was a tendency for risk of an infection to be decreased with adherence (odds ratio: 0.23; 95% CI: 0.05, 1.07; p = 0.06). Conclusion Adherence to the eTG was low (13.3%), despite a decreased risk of SSI when guidelines were followed.